Terror and Erebus by Gwendolyn MacEwen: White Technologies and the End of Science - Hulan, Renée (Nordlit, 2015)
This paper examines Canadian poet Gwendolyn MacEwen’s verse play Terror and Erebus by considering the play’s representation of technology in light of its own poetic technologies. Terror and Erebus is a play for voices that features four characters: Franklin, Crozier, Rasmussen, and Qaqortingneq. As the character Rasmussen searches for the traces of the lost expedition, imagining the voices of the explorers in their final hours, his investigation reveals how the “white technologies” used to explore the Arctic succumb to the environment without the indigenous knowledge possessed by the Inuit who inhabit the Arctic. The paper shows how MacEwen’s literary vision contrasts recent coverage of efforts to locate the Franklin ships which have ignored or down-played Inuit testimony. Working from Rasmussen’s transcriptions of Qaqortingneq’s voice, MacEwen represents Inuit knowledge and technology as both an alternative to the model of scientific discovery underwriting the Franklin expedition and as source of the authoritative account of what happened to Franklin and his crew.